Devising a method for assessing the level of transport services in the "People – Transport – Road – Environment" system - Melnychenko, Olexandr; Ignatenko, Oleksandr; Tsybulskyi, Vitalii; Chechuha, Oleksandr; Vyhovska, Inna; Derehuz, Igor; Alimov, Akim (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of assessing the level of public transport service provision in cities. The task is to devise a method for assessing the level of public transport service provision in terms of the influence of characteristics of the elements within the "People – Transport – Road – Environment" system. It was determined that these characteristics could serve as predictors – parameters and forecasting tools that determine the level of quality of public transport services for city residents. A logistic model has been built, which underlies the method for assessing the level of public transport service provision. This approach could allow for a comprehensive and interconnected study of social and technological factors of transport activity of subjects. A method for diagnosing the logistic model for adequacy and consistency with empirical data has been proposed, which is based on the application of the Hosmer-Lemeshov agreement criterion and ROC analysis. The method for assessing the level of public transport service provision was tested using an example of a city of regional significance. The adequacy of the method was confirmed using the Hosmer-Lemeshaw criterion and ROC analysis, which were 8.892 and 0.3428, respectively. Based on the verification results, proposals have been devised to improve the predictors of the activities of urban carriers. The effectiveness of the proposed measures was assessed by the percentage change in the time spent by city residents on travel, which was 17.5 %. This confirms the acceptability of the method devised. The scope of using the method includes activities of business entities that provide transport services to the people in cities and to local government bodies. The prospect of this study is its application to assessing the level of quality of transport services by other types of passenger transport